'Friending someone means just adding them to your friends list, not much else': Children's casual practices in virtual world games. (June 2017) - Willett, Rebekah
This article analyzes young preteens' uses and understandings of virtual world games, with a focus on the structures that create different online experiences. The study involved working with a group of 28 children aged 8 to 10 years. Data analyzed in this article are paper-based activities, semistructured interviews, and field notes. The article investigates dominant constructions of children as 'not yet complete' and as 'active, knowing beings' (Cook, 2005). These dichotomous constructions are explored across the literature concerning children and virtual world games, particularly in relation to online risks and opportunities. The analysis focuses on ways data collected for this project challenge constructions of children as either at risk or active and empowered. The analysis reveals that many children's online engagements in virtual world games are casual (i.e. they are not investing time or money in the games) and structured by factors such as age, socioeconomic status, and Internet access. The article suggests that studies of children online need to distinguish between different digital childhoods, particularly in relation to research and policy suggestions.